The Prognostic Impact of Combined Tumor-Infiltrating Lymphocytes and Pretreatment Blood Lymphocyte Percentage in Locally Advanced Nasopharyngeal Carcinoma - Cai, Zhuochen; Jiang, Jiali; Huang, Laiji; Yuan, Yawei; Zheng, Ronghui; Zhang, Jiangyu; Qiu, Wenze (Frontiers in Oncology, 2022)
Purpose: To explore the prognostic impact of combined tumor-infiltrating lymphocytes (TILs) and pretreatment peripheral lymphocyte percentage (LYM%) among patients with locally advanced nasopharyngeal carcinoma (LA-NPC). Patients and Methods: TILs and pretreatment LYM% were retrospectively assessed in 253 LA-NPC patients who underwent chemoradiation therapy between January 2012 and December 2017. According to TILs and LYM% status, the patients were divided into three groups: high-risk group (HRG) (TILs-LYM% score=0), middle-risk group (MRG) (TILs-LYM% score=1), and low-risk group (LRG) (TILs-LYM% score=2). The relationship between TILs level and LYM%, as well as the associations of TILs-LYM% status with clinicopathological factors and survival, were evaluated. Results: As a continuous variable, LYM% was significantly higher in TILs-high group. High TILs or high LYM% alone was significantly related to better 3-year disease-free survival (DFS), overall survival (OS), distant metastasis-free survival (DMFS) and locoregional relapse-free survival (LRRFS), respectively. Kaplan-Meier analysis and log-rank tests also revealed significant decreases in DFS, OS, DMFS and LRRFS among LA-NPC patients with TILs-LYM% score of 0, 1 and 2 (all P<0.05). Further multivariate analyses showed that TILs-LYM% score was an independent factor affecting patients’ survival, and HRG (TILs-LYM% score=0) had increased hazard ratios (HRs) for disease (HR=6.89, P<0.001), death (HR=8.08, P=0.008), distant metastasis (HR=7.66, P=0.001), and local relapse (HR=5.18, P=0.013) compared with LRG (TILs-LYM% score=2). In receiver operating characteristics (ROC) analyses, TILs-LYM% score had a higher area under the ROC curve (AUC) for the prediction of DFS than did TILs or LYM% alone. Conclusions: A positive correlation was found between TILs level and pretreatment blood lymphocyte percentage. Moreover, TILs-LYM% score can be considered as a novel independent prognostic indicator of survival outcome among patients with LA-NPC.